2001
DOI: 10.1016/s0030-4018(01)01498-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromophore–chromophore electrostatic interactions in the NLO response of functionalized organic–inorganic sol–gel materials

Abstract: In the last years, important non-linear optical results on sol-gel and polymeric materials have been reported, with values comparable to those found in crystals. These new materials contain push-pull chromophores either incorporated as guest in a high T g polymeric matrix (doped polymers) or grafted onto the polymeric matrix. These systems present several advantages; however they require significant improvement at the molecular level -by designing optimized chromophores with very large molecular figure of meri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…By molecular engineering towards large electrooptic molecular figures of merit (using a simple two-state twolevel model) and suitable thermal stability, and by controlling the intermolecular dipole±dipole interactions by tuning push± pull chromophore concentration, Blanchard-Desce et al [146] have recently shown the ability to prepare hybrid thin-films with very large electro-optic coefficients. For instance, using push±pull phenylpolyene chromophores grafted to the silica matrix with a lb eight times larger than that of DR1 and carbazole units to avoid dipolar chromophore interactions, this strategy has led to a very high electro-optic coefficient (r 33 ) of 48 pm V ±1 at 831 nm, [147] which is suitable for electro-optic applications. In summary, better results are generally obtained when NLO dyes are grafted to the oxide matrix via several covalent bonds (hybrids of class II).…”
Section: Second-order Nlo In Hybrid Materialsmentioning
confidence: 99%
“…By molecular engineering towards large electrooptic molecular figures of merit (using a simple two-state twolevel model) and suitable thermal stability, and by controlling the intermolecular dipole±dipole interactions by tuning push± pull chromophore concentration, Blanchard-Desce et al [146] have recently shown the ability to prepare hybrid thin-films with very large electro-optic coefficients. For instance, using push±pull phenylpolyene chromophores grafted to the silica matrix with a lb eight times larger than that of DR1 and carbazole units to avoid dipolar chromophore interactions, this strategy has led to a very high electro-optic coefficient (r 33 ) of 48 pm V ±1 at 831 nm, [147] which is suitable for electro-optic applications. In summary, better results are generally obtained when NLO dyes are grafted to the oxide matrix via several covalent bonds (hybrids of class II).…”
Section: Second-order Nlo In Hybrid Materialsmentioning
confidence: 99%
“…This shift slightly increases with chromophore concentration (i.e., 14 nm for P2 and 8 nm for P2*), a behaviour that may be ascribed to dipoledipole interactions leading to a multimeric association of chromophores. [15] More significantly, a decrease of absorbance is observable in the spectra of both copolymers after poling. Different mechanisms may account for this behaviour:…”
Section: Resultsmentioning
confidence: 95%
“…The superposition of the two bands appears as a blue-shift of the absorption band. During photoisomerization, the aggregates can be broken [12], trans molecules are freed, the number of molecules with the absorption maximum near the wavelength of the probe increases and this gives additional contribution to T 0 [6,13].…”
Section: Uv-visible Absorption: Dye Aggregationmentioning
confidence: 99%